Effects of Trichoderma viride and copper hydroxide on rhizome rot of ginger (Bangladesh Journal of Botany, 2021)
To assess the impact of rhizome rot disease management on growth and yield of ginger a study was carried out. Rhizome treatment with copper hydroxide resulted 86% ginger germination followed by Trichoderma viride which was 81% over local check. The results further revealed that rhizome treatment by copper hydroxide and its soil drenching effectively controlled rhizome rot disease (67%) with reduced disease incidence (4.6%) followed by Trichoderma viride which controlled the disease by 53.5% and reduced the disease incidence to 6.8% over local check. Extension and technology gap was recorded 2.5 and 3.8 t/ha. Raised bed planting, use of Trichoderma viride, disease free seed and rhizome treatment were adopted by 53.3, 26.6, 29.3 and 24% respondents.